2012
DOI: 10.1017/s1743921312019503
|View full text |Cite
|
Sign up to set email alerts
|

A systematic search for rapid photometric variability in southern symbiotic stars I. V648 Car

Abstract: Abstract. We present the first results from the systematic observational campaign aimed at studying rapid photometric variability (i.e., flickering) in southern symbiotic stars. In particular, we report on the discovery of strong flickering from V648Car (also known as SS73-17), a poorly studied system belonging to the small class of hard X-ray emitting symbiotic stars. To our knowledge, with a U-band flickering amplitude >0.6mag over time scales of minutes, it is one of the most significant flickering ever rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Systematic searches for flickering variability in symbiotic stars and related objects (Angeloni et al ; Dobrzycka et al ; Gromadzki et al ; Sokoloski et al ; Stoyanov ) have shown that, among the more than 200 symbiotic stars known, only in 10 objects flickering activity is detected: that is, RS Oph, T CrB, MWC 560, Z And, V2116 Oph, CH Cyg, RT Cru, o Cet, V407 Cyg, and V648 Car.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic searches for flickering variability in symbiotic stars and related objects (Angeloni et al ; Dobrzycka et al ; Gromadzki et al ; Sokoloski et al ; Stoyanov ) have shown that, among the more than 200 symbiotic stars known, only in 10 objects flickering activity is detected: that is, RS Oph, T CrB, MWC 560, Z And, V2116 Oph, CH Cyg, RT Cru, o Cet, V407 Cyg, and V648 Car.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic searches for flickering variability in symbiotic stars and related objects (Dobrzycka, Kenyon & Milone 1996;Sokoloski, Bildsten & Ho 2001;Gromadzki et al 2006;Angeloni et al 2013) have shown that optical flickering is a rarely detectable phenomenon in symbiotic stars. Among more than 200 symbiotic stars known, only in 11 objects flickering activity is visible.…”
Section: Introductionmentioning
confidence: 99%